Peer Learning for Inclusive Growth: A Cross-National Study of Thailand and Indonesia - Hery Rahmat; Ika Rama Suhandra; Eliya Eliya; Siwapoorn Yuenchon (Journal of English Language Teaching Fakultas Pendidikan Bahasa dan Seni Program Studi Pendidikan Bahasa Inggris IKIP Mataram)
Peer learning has been widely recognized as an effective strategy in inclusive education, promoting student collaboration, enhancing academic outcomes, and addressing diverse learning needs. However, a significant gap remains in understanding how peer learning is implemented across different institutional and national contexts, especially in inclusive settings. While prior studies have addressed peer learning in general, few have compared its practical application across countries with distinct educational systems. This study investigates how peer learning is enacted in inclusive classrooms in Thailand and Indonesia, focusing on teachers’ beliefs, instructional strategies, and challenges encountered during implementation. Employing a qualitative research design, data were gathered through interviews and classroom observations to explore authentic classroom practices. The findings reveal both shared patterns and contextual differences in the use of peer learning, shaped by each country’s institutional structures and education policies. While initial student collaboration varied, many learners demonstrated increased participation and interaction over time. This study addresses the lack of cross-national research on inclusive peer learning and offers insights that may support educators, researchers, and policymakers in designing more responsive and culturally informed frameworks for peer learning in diverse, inclusive classrooms.